Peranan Penting Digital Marketing dalam Promosi Produk UMKM Di Kalangan Mahasiswa Fakultas Ekonomi - Yupiter Mendrofa; Crisman Tri Boy Ndraha; David Warisman Waruwu; Deli Asni Laoli; Ferdinand Pangestu Dohona; Firmus Albert Foera Era Daeli; Jefri Hardin Laoli; Melkisan Mahatma Ranggi Zebua; Wahyu Asrianja Zebua (LPPM Universitas HKBP Nommensen, 2025)
The development of digital technology offers great opportunities for MSMEs to increase competitiveness, especially in product promotion. This community service aims to identify the strategic role of digital marketing in student and MSME business promotion and to describe the contribution of Faculty of Economics students as agents of change. The method used is literature review and descriptive qualitative approach. The results show that digital marketing provides a wide market reach, cost efficiency, and consumer interaction capabilities. Faculty of Economics students have great potential in assisting MSMEs’ digitalization through training and mentoring. This study concludes that collaboration between academia and MSMEs is essential in advancing the digital economy.